Inhibitory Effect of Bacteriophages Isolated from Sewage Water in the City of Kirkuk on some Types of Human Pathogenic Bacteria (Baghdad Science Journal, 2025)
Most approaches to combat antibiotic resistant bacteria concentrate on discovering new antibiotics or modifying existing ones. However, one of the most promising alternatives is the use of bacteriophages. This study was focused on the isolation of bacteriophages that are specific to some of commonly human pathogens namely E. coli, Streptococcus pyogenes, Staphylococcus aureus, Proteus mirabilis, Pseudomonas aeruginosa, Salmonella spp. and Klebsiella pneumoniae. These bacteriophages were isolated from sewages that were collected from four different locations in Kirkuk City. Apart from S. pyogenes, bacteriophages specific to all tested bacteria were successfully isolated and tested for their effectiveness by spot test. The most effective bacteriophages that were isolated from sewages and sewage water of Al-Jumhori Hospital compared to other sites. It is concluded that the sewage water of hospitals represents a perfect environment for these bacteriophages.